? asked in Science & MathematicsMathematics · 1 decade ago

Solve the Given Equation?

y^2 + 3 = y(4-y)

Please show how you get your answer. thank you.

1 Answer

Relevance
  • Nuzhah
    Lv 5
    1 decade ago
    Favorite Answer

    y^2 + 3 = y(4-y)

    y^2 +3=4y-y^2

    y^2+y^2-4y+3=0

    2y^2-4y+3=0

    solve using quadradic formula

    you will get

    y=

    4+sqrt -32

    ------------

    4

    =4+ sqrt 32i^2

    -------------------

    4

    =4+4i sqrt2

    ----------------

    4

    =1+i sqrt 2

    or

    you will get

    y=

    4-sqrt -32

    ------------

    4

    =4- sqrt 32i^2

    -------------------

    4

    =4-4i sqrt2

    ----------------

    4

    =1-i sqrt 2

    ans=

    y=1+isqrt2

    y=1-isqrt2

    note

    sqrt -1=sqrt i^2

    sqrt -32=sqrt 32i^2

Still have questions? Get your answers by asking now.